2017
DOI: 10.1016/j.cmet.2017.04.003
|View full text |Cite|
|
Sign up to set email alerts
|

Deciphering Pancreatic Islet β Cell and α Cell Maturation Pathways and Characteristic Features at the Single-Cell Level

Abstract: Pancreatic β and α cells play essential roles in maintaining glucose homeostasis. However, the mechanisms by which these distinct cell populations are generated, expand, and mature during pancreas development remain unclear. In this study, we addressed this critical question by performing a single-cell transcriptomic analysis of mouse β and α cells sorted from fetal to adult stages. We discovered that β and α cells use different regulatory strategies for their maturation and that cell proliferation peaks at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
143
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 86 publications
(116 reference statements)
11
143
0
Order By: Relevance
“…To obtain differentiated a cells, we generated a Gcg-P2A-GFP mouse strain ( Fig EV1C) in which a-cell identity was validated by immunostaining of glucagon in islets ( Fig EV1D) and by sc-RNA-seq of E17.5 GFP + cells from this strain. Principal component analysis (PCA) showed that these cells clustered with the E17.5 a cells sequenced in our previous study (Qiu et al, 2017a; Fig EV1E). Therefore, this Gcg-P2A-GFP mouse strain can be used to label a cells.…”
Section: Isolation Of Cell Lineages From Fetal Pancreas For Sc-rna-seqmentioning
confidence: 57%
See 3 more Smart Citations
“…To obtain differentiated a cells, we generated a Gcg-P2A-GFP mouse strain ( Fig EV1C) in which a-cell identity was validated by immunostaining of glucagon in islets ( Fig EV1D) and by sc-RNA-seq of E17.5 GFP + cells from this strain. Principal component analysis (PCA) showed that these cells clustered with the E17.5 a cells sequenced in our previous study (Qiu et al, 2017a; Fig EV1E). Therefore, this Gcg-P2A-GFP mouse strain can be used to label a cells.…”
Section: Isolation Of Cell Lineages From Fetal Pancreas For Sc-rna-seqmentioning
confidence: 57%
“…The simultaneous principal curves indicate the developmental pathways of these cells. Data on E17.5-P60 quiescent b and a cells from our published study (Qiu et al, 2017a) were integrated into this PCA. F…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, ATAC-seq and the mRNA microarray analyses have been performed in whole islets and not in FACS-sorted cells or in single cells. Several recent studies have demonstrated a large heterogeneity of gene expression at a single cell level using smFISH or single cell RNA-seq (45)(46)(47)(48). Taking advantage of the heterogeneity of gene expression together with single cell ATAC-seq could shed more light on the transcriptional control of islet maturation and the different cell types involved.…”
Section: Discussionmentioning
confidence: 99%